Acumulação tecnológica e aprimoramento de performance competitiva: evidências de diferenças e similaridades e médias empresas do setor metal-mecânico no estado do Rio de Janeiro - Martins, Newton (2007)
The main objective of this dissertation is to examine the implications of technological capacities in the improvement of technical performance indexes, specifically at the company level. These relationships were examined in a small sample of metal-working enterprises in the state of Rio de Janeiro (1960 to 2006). Although diverse studies on technological competences have been carried out in the last twenty years, a gap in empirical studies still exist that correlate the performance of companies in the context of developing countries, especially in Brazil. Aiming to contribute to a reduction of these gaps, this dissertation examines the questions by the light of available models in literature, which opting themselves to using operational indexes of companies. For drawing the accumulation of technological competences in this study, the metric proposal by Figueiredo (2000) shall be used indicating the levels of technological qualification in process, product, and equipment functions. The empirical evidence examined in this dissertation is both qualitative and quantitative in nature and were collected, first hand, through extensive field research involving informal interviews, meetings, direct-site observation and document analysis. In relation to the results, the evidence suggests that: - In terms of technological accumulation, a company reached Level 5 of technological capacity in process and organization of production as well as product and equipment. Three companies obtained Level 4 in the function process function while two others had reached the same technological level in the functions of product and equipment. Two companies had reached Level 3 in the product and equipment functions and one remained this level in the function of process; - In terms of the rate of accumulation of technological capacities, the observed companies had reached Level 4 needs 29 years in process function, 32 years in product function and 29 years in equipment function; - In terms of improvement performance pointers, a company which reached Level 5 of technological capacity improved in 70% of its indicators of performance, while the company that had achieved Level 4 had raised its pointers 60% and the other companies had gotten improved in the order of 40%. It was evidenced that the majority of the pointers of the companies with higher levels of technological capacities had obtained better performance. This dissertation contributes to advancing the strategic management of companies in metal-working segment to understanding internal accumulation of technological capacity and indicators of performance especially in the field of empirical context studied. This information offers management examples of how to improve competitive performance through the accumulation of technological capacities in the process, product and equipment functions.